Retrograde device-assisted lumen-apposing metal stent insertion for candy cane syndrome - Anne Kimberly Lim-Fernandez, MD; Samuel Jun Ming Lim, MRCP; Chin Hong Lim, MRCP; Christopher Jen Lock Khor, MRCP; Damien Meng Yew Tan, MRCP (VideoGIE)
Background and Aims: Candy cane syndrome is a rare adverse event of gastric bypass or gastrectomy, where a blind jejunal pouch fills with food, causing dilation and compression of the efferent limb, leading to obstructive symptoms like vomiting and regurgitation. Surgical resection is curative but technically challenging, and endoscopic treatment using lumen-apposing metal stent (LAMS) insertion has been attempted. Methods: This case describes a retrograde LAMS insertion in a patient with previous total gastrectomy who presented a decade later with dysphagia and food regurgitation. Imaging revealed an enlarged blind jejunal pouch and migration of the esophagojejunostomy anastomosis above the diaphragm and into the thoracic cavity. A tandem endoscopic approach with an ultraslim gastroscope and an echoendoscope was used to place a LAMS from the efferent limb into the blind pouch. The gastroscope is used to assist with instillation of saline and endoscopic visualization of the LAMS in the blind pouch to ensure safe deployment. A retrograde approach from the efferent limb to the blind pouch allows a larger and more stable target for puncture, and a better LAMS axis for effective diversion of food. Results: He gained 9 kg over 4 months after the procedure and was able to tolerate a normal diet. The LAMS was planned for removal after 10 to 12 months to allow longer indwelling time and greater rate of patency. Conclusions: Endoscopic management with EUS-guided LAMS insertion is a promising alternative to surgical resection for candy cane syndrome.